The use of mobile devices in‐store and the effect on shopping experience: A systematic literature review and research agenda - Cavalinhos, S. (2021)
The use of mobile devices continues to change the in‐store shopping experience and constantly increases curiosity among academics and retailers. However, in spite of the emergence of studies on this topic, the information about the effects of their use is still scattered. The aim of this research is to provide an overview on what is currently known about the effect of the use of mobile devices in‐store on the shopping experience, and describe the most important findings. Furthermore, future research directions are also provided in order to extend the existing knowledge. This systematic literature review has analysed a top‐quality poll of papers, published in the past decade. As a result, it contributes to a better understanding of this focal phenomenon by analysing the different types of use and the value added to the shopping experience. Our framework provides a systematization of these findings.